2019
DOI: 10.1088/1742-6596/1372/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Benign and Malignant Breast Cancer using Supervised Machine Learning Algorithms Based on Image and Numeric Datasets

Abstract: Breast cancer has been identified as the second leading cause of death among women worldwide after lung cancer and hence, it becomes extremely crucial to identify it at an early stage, which can considerably increase the chances of survival. The most important part in cancer detection is to be able to differentiate between benign and malignant tumors and this is where the work of Machine Learning comes in. Taking all the dependent features upon consideration, Supervised Machine Learning methods allow for class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Ray et al [20] explored different classification methods (Gaussian NB, kNN, DT, RF) for detecting breast cancer involving both numeric and image datasets. It was found that the accuracy of RF was better in both numeric and image datasets.…”
Section: Related Research Workmentioning
confidence: 99%
“…Ray et al [20] explored different classification methods (Gaussian NB, kNN, DT, RF) for detecting breast cancer involving both numeric and image datasets. It was found that the accuracy of RF was better in both numeric and image datasets.…”
Section: Related Research Workmentioning
confidence: 99%
“…The major types of BC surgeries are Lumpectomy, Mastectomy, Sentinel Node Biopsy, Axillary Lymph Node Dissection and Contralateral Prophylactic Mastectomy [4]. The common types of BC are DCIS (Ductal Carcinoma In-Situ), LCIS (Lobular Carcinoma In-Situ), Invasive Ductal Carcinoma(IDC) and ILC (Invasive Lobular Carcinoma) [5]. The WSI (Whole Slide Imaging) are mainly utilized in the eld of clinical education and digital image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to these clinical BC detection practices, Machine Learning (ML) has been proven as a promising tool for classifying benign and malignant tumors providing higher accuracy than physicians. At the same time, these techniques decrease the rate of misdiagnosis, which can account for up to almost 20% of diagnostic cases [12]. Nonetheless, misclassification is still a threat leading to harmful consequences for patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, FP classification is associated with severe negative physical and mental consequences for the misdiagnosed patients [13]. As a result of these misclassifications, ML models require special attention to class imbalance by applying various approaches such as adequate sampling strategies, evolution metrics, or classification algorithms [12]- [15].…”
Section: Introductionmentioning
confidence: 99%